Implementation of Risk Management at Jatiluwih Space Venue in Jatiluwih Village, Tabanan, Bali (Case Study of Jatiluwih Cultural Week 2022) - Anggita Dewi, Ni Wayan Anggita Dewi; Ariasri , Nyoman Reni; Widaharthana, I Putu Esa (Jurnal Pariwisata Nusantara (JUWITA), 2024)
Purpose: This study aims to examine the implementation of risk management at the Jatiluwih Space venue, focusing on the case study of Jatiluwih Cultural Week 2022. Method: The research method used is qualitative, utilizing ISO 31000:2018 as a reference framework, which includes seven indicators: communication and consultation, context establishment, risk identification, risk analysis, risk evaluation, risk treatment, and monitoring and review. Data were collected through observations and in-depth interviews with seven informants. Result: The findings indicate that the organizers implemented risk management based on ISO 31000:2018 during the Jatiluwih Cultural Week 2022. This included discussions related to venue risks, the establishment of roles and responsibilities, the development of risk identification steps, and the determination of risk levels through the cross-multiplication of probability and impact ratings, resulting in the identification of two levels of risk: low and medium. Contribution: This research contributes by providing an example of ISO 31000:2018-based risk management implementation during the Jatiluwih Cultural Week 2022. The organizers successfully identified and assessed risks using appropriate methods, allowing them to manage risks at low to medium levels. These findings can serve as a practical reference for similar events in effectively implementing risk management.